Assistance in Moringa Plant Cultivation Techniques with Stem Cuttings Method in Several Combinations of Planting Media in Kuta Blang Village, Samadua District, South Aceh - Maisuri Suri; Dewi Junita; Sumeinika Fitria Lizmah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Kuta Blang is one of the villages in the Sedar Settlement, Samadua District, South Aceh Regency. Based on observations, the yard of the house in Kuta Blang Village has not been used properly. In addition, in the village of Kuta Blang found a lot of organic waste that can be used for planting media. One of the plants that have the potential to be used in the yard of the household is the Moringa plant. The purpose of this service activity is to increase the understanding and skills of the people of Kuta Blang Village regarding the technique of cultivating Moringa plants with the stem cutting method on several combinations of planting media in an effort to utilize waste and household yards. The people of Kuta Blang Village were very enthusiastic about participating in the activity which began with outreach activities and practical activities for growing Moringa plants using the stem cuttings method in several combinations of planting media.